Historiographic and Biographic Accounts of Danish Deaconesses Serving in the Faroe Islands 1897–1948 ... - Hall, Elisabeth; Lund Joensen, Annemie; Malchau Dietz, Susanne (European Journal for Nursing History and Ethics, 2023)
The Faroe Islands are an archipelago of 18 islands situated in the middle of the North Atlantic Ocean. Basic organized nursing there began in the late 1890s with arrival of two Danish deaconesses sent to the islands to improve the population’s health and move Faroese nursing and nurse education closer to international standards. Twenty-five Danish deaconesses served in the Faroe Islands during the first half of the 1900s. The overall aim of this article is to contribute to nursing history about the deaconesses in the Faroe Islands. In caring and historic contexts, and using historiographic and biographic approaches, we present and discuss excerpts of letters from some of the Danish deaconesses, in which they discuss their daily work, life, and ethical dilemmas while in the Faroe Islands. Findings demonstrate that the deaconesses were nurse pioneers, establishing professional nursing and nurse education fol¬lowing Danish rules and regulations of the time. We conclude by emphasizing the meaning of the ...